629.423.1 Development of a program for determining eccentricity by analyzing the magnetic field in the air gap of an asynchronous motor - Vokhidov, Mirabror (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article examines the work on identifying motor defects by calculating the magnetic field in the air gap of asynchronous motor used in railway rolling stock at industrial enterprises. The software for calculations and visualization is programmed in Python, and its analysis is presented.